2018
DOI: 10.3389/fpls.2018.00620
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of Markers Linked in Coupling for Tetraploid Potatoes via Monoparental Haploids

Abstract: Haploid potato populations derived from a single tetraploid donor constitute an efficient strategy to analyze markers segregating from a single donor genotype. Analysis of marker segregation in populations derived from crosses between polysomic tetraploids is complicated by a maximum of eight segregating alleles, multiple dosages of the markers and problems related to linkage analysis of marker segregation in repulsion. Here, we present data on two monoparental haploid populations generated by prickle pollinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…In addition, 50 tetraploid potato cultivars were used to determine the diagnostic value of selected molecular markers developed in this study. The pollinations with the dihaploid inducers were performed in a greenhouse on emasculated `Karolin´ flowers (Bartkiewicz et al 2018 ). The seeds of the cross of `Karolin´ and S. phureja IVP35 were preselected based on the occurrence of an embryo spot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 50 tetraploid potato cultivars were used to determine the diagnostic value of selected molecular markers developed in this study. The pollinations with the dihaploid inducers were performed in a greenhouse on emasculated `Karolin´ flowers (Bartkiewicz et al 2018 ). The seeds of the cross of `Karolin´ and S. phureja IVP35 were preselected based on the occurrence of an embryo spot.…”
Section: Methodsmentioning
confidence: 99%
“…The parental genotypes were genotyped with two repeats. Custom genotyping was performed by Neogene Genomics (Neogene Genomics, Lincoln, Nebraska, USA) and has been described previously in Bartkiewicz et al ( 2018 ). The SNP array results were validated using the following Kompetitive Allele Specific PCR (KASP) markers of the SNP markers that were most significantly linked to potato wart resistance: solcap_snp_c2_33740, solcap_snp_c2_33712, solcap_snp_c1_4319, solcap_snp_c1_4322, solcap_snp_c2_6082, solcap_snp_c2_6287, solcap_snp_c1_2275, solcap_snp_c2_6309 and solcap_snp_c2_6285.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of small introgressions is more challenging. Recent genotyping (Bartkiewicz et al 2018) or sequencing (Pham et al 2019) of other dihaploid potato populations found that ~1% of SNP loci displayed presence of HI DNA in very small tracts and with lower than expected allelic ratio. As in these reports, we detected many, widely dispersed SNP represented by proportionally fewer aligned reads than expected for addition of a haploid inducer DNA segment, or alternatively, replacement of a non-HI haplotype by homologous recombination.…”
Section: Genetic Contribution From Haploid Inducer Not Detected Despimentioning
confidence: 99%
“…In potato ( Solanum tuberosum L.), the world's fourth most important crop in terms of calories consumed per person per day ( http://www.fao.org/faostat/en/#compare ), haploid seed can be routinely obtained via pollination with select haploid inducer varieties from the diploid S. tuberosum Andigenum Group (formerly S. tuberosum Phureja Group or S. phureja (Spooner et al 2014) . Such crosses with tetraploid potato (2n=4x=48) produce 2 n =2 x =24 dihaploids that can be used for genetic mapping (Kotch et al 1992;Pineda et al 1993;Ercolano et al 2004;Velásquez et al 2007;Mihovilovich et al 2014;Bartkiewicz et al 2018) . Additionally, these crosses produce hybrids that can be either triploid or tetraploid (Wagenvoort and Lange 1975;Hanneman and Ruhde 1978) , and can be identified as seed because they express a purple embryo spot, a dominant anthocyanin marker encoded by the haploid inducers that is expected to be absent in the dihaploids (Fig.1) (Hermsen and Verdenius 1973a) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation